2012
DOI: 10.1038/gim.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

The emerging phenotype of long-term survivors with infantile Pompe disease

Abstract: Purpose Enzyme replacement therapy with alglucosidase alfa for infantile Pompe disease has improved survival creating new management challenges. We describe an emerging phenotype in a retrospective review of long-term survivors. Methods Inclusion criteria included ventilator-free status and age ≤6 months at treatment initiation, and survival to age ≥5 years. Clinical outcome measures included invasive ventilator-free survival and parameters for cardiac, pulmonary, musculoskeletal, gross motor and ambulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 32 publications
7
146
1
1
Order By: Relevance
“…A potential clinical correlate is evidence of preexcitation on electrocardiograms for case 1 and shortened conduction time in a postmortem electrogram on bundle of His tissue (Nakamura et al 1979). Several longterm survivors have experienced arrhythmias (McDowell et al 2008;Prater et al 2012), and we propose that cardiac conduction is affected by glycogen accumulation within the conduction system. Glycogen accumulation in the cardiac conduction system is present in glycogen storage disease type III and in the mouse model for PRKAG2-caused hypertrophic cardiomyopathy (Austin et al 2012;Arad et al 2003).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A potential clinical correlate is evidence of preexcitation on electrocardiograms for case 1 and shortened conduction time in a postmortem electrogram on bundle of His tissue (Nakamura et al 1979). Several longterm survivors have experienced arrhythmias (McDowell et al 2008;Prater et al 2012), and we propose that cardiac conduction is affected by glycogen accumulation within the conduction system. Glycogen accumulation in the cardiac conduction system is present in glycogen storage disease type III and in the mouse model for PRKAG2-caused hypertrophic cardiomyopathy (Austin et al 2012;Arad et al 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Some of the complications, such as bowel and urinary incontinence, arterial aneurysms, and dysphagia, overlap with known complications in late-onset Pompe disease (LOPD) (El-Gharbawy et al 2011;Prater et al 2012;Hobson-Webb et al 2012;Laforêt et al 2008). Additional findings, such as cardiac arrhythmias and ocular refractory errors, are emerging (Prakalapakorn et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that patients with HSAT respond poorly and experience clinical decline despite ERT. Additional factors, such as the age and the stage of disease at ERT initiation, also contribute to clinical outcome [45,46]. A recent study that focused only on the treatment outcomes of CRIM-negative patients also suggested that the majority but not all of CRIM-negative patients mounted a significant immune response [47].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There are now teenagers living with IPD [45]. Although there are challenges with the current ERT, the importance of this lifesaving therapy cannot be overemphasized.…”
mentioning
confidence: 99%
“…22 Current treatment with enzyme replacement therapy (ERT) is very effective in restoring cardiac function and extending the life span of infants, but it fails to significantly reverse or halt the progression of the disease in skeletal muscle. [23][24][25] We have previously shown in the Gaa-KO mouse model that in addition to the enlargement of glycogen-loaded lysosomes, abnormal autophagy, accumulation of autophagic substrates, and impaired autophagosomal-lysosomal fusion greatly contribute to the pathogenesis of muscle damage and to muscle resistance to ERT. 26,27 We have recently established yet another abnormality in the diseased muscle-the accelerated production of large, unrelated-to-aging lipofuscin deposits-a marker of oxidative damage and a sign of mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%